DEVELOPMENT AND IMPLEMENTATION OF CREATIVITY-ORIENTED TEACHING STRATEGY - S. N. Degtyarev (Образование и наука)
The research investigates the principles of creativity-oriented teaching (COT), substantiates its strategy based on developing the didactic structure of creative educational environment, and looks for the invariant of pedagogical activity guaranteeing the creativity development. The methodology involves a theoretical analysis and specification of COT principles, and empirical methods of identifying the creative teaching invariant.The paper describes the content of COT principles, and provides recommendations for their implementation; the concepts of creative teaching invariant and creative potential being defined. The author supplements the theory of heuristic teaching and applies the methods of logical and graphical structuring of information to foster students’ creative activity.The research findings can be implemented in the system of school education for developing the students’ intellectual potential and creative abilities.